The Implementation of Scientific Approach in Teaching English at SMP Negeri 38 Medan - Roni Juliansyah; Masniati Murni Ritonga (Universitas Islam Sumatera Utara, 2023)
This research was to describe the implementation of scientific approach and the problems in teaching English. The writer used qualitative research. Subjects of this research were English teachers of SMP Negeri 38 Medan.The data of this research were collected by relating observation, interview and documentation. The data were evaluated by applying data reduction, data display, and conclusion based on Miles and Hubberman (1994). The findings showed that the teachers used scientific approach covering the activities were as follows, (1) in the observing activity, teachers showed prohibition images, English instructions and introduced in English, (2) in the activity of asking, there was activity of asking and answering about the observed objects., (3) in the activity of experimenting, the teachers guided the students to demonstrate, discuss and try, (4) in the activity of associating, the teachers guided the students to conduct English exercise, (5) in activity of communicating, students present orally. Meanwhile there were problems faced by the teachers as follows, (1) lack of attractive media in the observing activity, (2) lack of students’ activiness, (3) lack of students’ self-confidence and partaking to experience, (4) lack of students’ vocabulary, (5) and lack of students’ responsiveness.